Osteoclastogenesis regulatory factors (RANK, RANKL and OPG) in osteolytic jaw lesions - Moraes, Maiara de (2013)
Receptor activator of nuclear factor κB (RANK), RANK ligand (RANKL) and osteoprotegerin (OPG) are members of the superfamily of ligands and receptors of tumor necrosis factor relationed with bone metabolism. Osteoclastogenesis is regulated by these three proteins. The aim of this review was to assess the immunohistochemical expression of these proteins in osteolytic jaws lesions. Studies were identified by searching MEDLINE/Pubmed. The results link higher imunoexpression for RANKL compared to OPG in chronic periodontitis and in aggressive odontogenic tumors, and in less aggressive odontogenic tumors a tendency for higher expression for OPG. Taken into account this, OPG could be a good candidate for the treatment of oral lesions can often be widely destructive.